Utilization of Kenar (Kleinhovia Hospita) Leaf Extract as Eye Drops in the Treatment of Malaria: A Case Study in Manusa Village - LATTU, JOMA CHYNTIA; Adi, Mateus Sakundarno; Sutiningsih, Dwi (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Malaria remains a public health challenge in eastern Indonesia, especially in remote areas like Manusa Village, where access to healthcare is limited. The community relies on traditional treatment using eye drops made from Kenar leaves (Kleinhovia hospita L.). The purpose of this study is to explore, from an epidemiological perspective, the use of Kenar leaves as a primary component in the formulation of traditional malaria remedies within the community of Manusa Village is lacking.Methods: This study employed a quantitative descriptive design with a cross-sectional approach. Data were obtained through structured questionnaires and phytochemical analysis of Kenar leaves. A total of 102 respondents voluntarily participated in the study.Results: Among respondents from 102 respondents, 67,6% had experienced malaria, and 68,6% reported using Kenar leaf eye-drops. Use was significantly associated with prior malaria history (POR = 15,057; p < 0,001) and age group 26-45 years (POR = 17,813; p < 0,001). Conversely, respondents with current malaria symptoms were less likely to use the drops (POR = 0,042; p = 0,002). Twice-weekly use was associated with better recovery outcomes (POR = 0,168; p = 0,003). The majority (84,3%) reported mild side effects, such as transient eye irritation. Phytochemical analysis confirmed the presence of alkaloids, flavonoids, steroids, and tannins compounds with known antimalarial properties.Conclusion: This study provides new evidence linking traditional knowledge and community-based practices with malaria self-treatment, highlighting implications for health promotion strategies.